EFFICACY OF DIFFERENT SEED TREATMENTS AGAINST Aspergillus niger - N. AISWARYA*, S. L. BHATTIPROLU, K. BAYYAPU REDDY and G. RAMA RAO (The Journal of Research ANGRAU, 2022)
Efficacy of various fungicides and bio-control agents against Aspergillus niger affecting groundnutwas tested. Groundnut seed of 13 varieties viz., Abhaya, Amaravati, Chitravati, Dharani, Haritandhra,ICGV 00 350, Kadiri 6, Kadiri 9, Narayani TAG 24, TCGS 1073, TCGS 1616 and TCGS 1694 wasartificially inoculated by soaking in conidial suspension of A. niger @ 106 conidia ml-1 for 20 min, driedat room temperature and then treated with fungicides viz., mancozeb @ 3 g kg-1, carbendazim @ 2 gkg-1, tebuconazole @ 1 g kg-1, carboxin+thiram @ 2 g kg-1; bio-control agents, Trichoderma viride @10 g kg-1 and Pseudomonas fluorescens @ 10 g kg-1. The inoculated seed of different treatmentswere incubated in rolled paper towels for 10 days. Of all the fungicides and bio-control agents testedtebuconazole recorded highest germination (91.04%) and maximum disease control (90.29%),whereas, carbendazim recorded highest seedling length (18.44cm), seedling vigour index I (1660),seedling dry weight (0.22) and seedling vigour index II (19.48).